Enhancing Self-Regulated Learning and Conceptual Understanding through a TPACK-Based Physics E-Module on Momentum and Impulse - Reski, Andi; Sari, Desy Kumala; Uskenat, Kristina; Jua, Selestina Kostaria (Universitas Muhammadiyah Makassar, 2025)
Physics learning frequently poses challenges for students due to the abstract nature of its concepts, particularly in topics such as momentum and impulse, which often result in misconceptions and low engagement. In response to this urgency, integrating technology through the Technological Pedagogical Content Knowledge (TPACK) framework has been advocated as an effective strategy to improve conceptual understanding and foster self-regulated learning (SRL). This study aimed to evaluate the effectiveness of a TPACK-based physics e-module in simultaneously enhancing students’ conceptual comprehension and SRL. Employing a quasi-experimental one-group pretest–posttest design, the research involved 30 students at SMA Negeri 2 Merauke, Indonesia. Instruments included a 20-item multiple-choice test on momentum and impulse concepts and a 20-item SRL questionnaire, both validated using Gregory’s content validity index (CVI > 0.80) and demonstrating strong reliability (Cronbach’s alpha > 0.80). Data analysis comprised descriptive statistics, normality testing, paired-sample t-tests, effect size calculations, and normalized gain (N-Gain) indices. The results indicated significant improvements in both domains: SRL scores increased from a mean of 66.50 to 82.50 (t = -12.24; p<0.001; d = 1.49; N-Gain = 0.449), while conceptual understanding improved from 46.30 to 73.00 (t = -18.21; p<0.001; d = 1.62; N-Gain = 0.497). These findings confirm that the e-module effectively addressed both cognitive and metacognitive aspects of learning. The novelty of this study lies in its dual focus on SRL and conceptual mastery within a single intervention, applied in a frontier educational context. The study contributes to physics education by providing empirical evidence of TPACK’s capacity to deliver scalable, context-sensitive innovations that enhance learning outcomes in diverse settings.